2019
DOI: 10.5937/gp23-22680
|View full text |Cite
|
Sign up to set email alerts
|

Heat-related mortality as an indicator of population vulnerability in a mid-sized Central European city (Novi Sad, Serbia, summer 2015)

Abstract: Hot summers with several intensive heat waves lead to strong heat-related mortality in Central and Southeast European cities. Therefore, the aim of the study was to evaluate association between maximum temaprature and mortality during the summer period in 2015 and to contribute to the future long-term assessment of heat-related mortality in urban population. The daily number of deaths of all causes and cause-specific mortality for the population of Novi Sad were used, as well as hourly air temperature data fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(3 citation statements)
references
References 61 publications
0
3
0
Order By: Relevance
“…Nevertheless, an abatement of this decline, possibly related to increased frequency and intensity of heatwaves and changes in the population age structure, has been documented recently (Urban et al, 2017;Urban et al, 2020). This has been supported by studies from other Central-European regions that reported significant impact of recent heatwaves on mortality in Germany (Muthers et al, 2017), Slovakia (Výberči et al, 2018), small Czech cities (Arsenović et al, 2019a) and Serbia (Arsenović et al, 2019b). Central-European cities, including Prague, the Czech Republic's capital, have recently been identified as cities with the largest increases in daily maximum temperatures by the end of the century under the high impact (RCP8.5) climate change scenario (Guerreiro et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…Nevertheless, an abatement of this decline, possibly related to increased frequency and intensity of heatwaves and changes in the population age structure, has been documented recently (Urban et al, 2017;Urban et al, 2020). This has been supported by studies from other Central-European regions that reported significant impact of recent heatwaves on mortality in Germany (Muthers et al, 2017), Slovakia (Výberči et al, 2018), small Czech cities (Arsenović et al, 2019a) and Serbia (Arsenović et al, 2019b). Central-European cities, including Prague, the Czech Republic's capital, have recently been identified as cities with the largest increases in daily maximum temperatures by the end of the century under the high impact (RCP8.5) climate change scenario (Guerreiro et al, 2018).…”
Section: Introductionmentioning
confidence: 74%
“…Given the outline of conditions presented above, it follows that city populations are often at heat-related risk. Several studies indicate that heat stress is becoming more frequent, with associated increases in hospitalization and mortality among vulnerable groups, such as people with pre-existing chronic complaints (e.g., cardiovascular and/or respiratory diseases), children (under the age of 18) and the elderly (those aged 65 and over) [13][14][15][16][17]. Furthermore, Wouters et al [18] predicted that the increases in heat stress in certain large European cities will be double those in their natural surroundings by 2050.…”
Section: Introductionmentioning
confidence: 99%
“…The result is an emerging phenomenon of urban heat islands in urban areas, characterized by an increase in air temperature in densely built-up central areas relative to undeveloped areas. Along with increasing heat waves in recent years, it is a serious problem from the human comfort and health point of view, especially in relation to vulnerable groups (elderly and sick people, young children) [1][2][3]. Extensive research conducted in four districts with different urban development patterns and geographic conditions in Shanghai indicated the local interplay between urban heat islands and heat waves [4].…”
mentioning
confidence: 99%